Designing Confidential Cloud Computing for Multi-Dimensional Threats and Safeguarding Data Security in a Robust Framework - Bande, Vasavi; Raju, B. Deevena; Rao, Karu Prasada; Joshi, Suneet; Bajaj, Sonia H.; Sarala, V. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In the dynamic landscape of cloud computing, robust security is imperative to safeguard sensitive data from cyber threats. Protecting against unauthorized access and ensuring data integrity are fundamental fostering trust and reliability in cloud services. Cyber-attacks on clouds often start with tricks like phishing or spreading harmful software. Weak passwords, mistakes in settings, or outdated systems make it easy for hackers. Once they get in, they may steal data or harm shared resources. They try to gain more control and cause damage. Stopping these attacks needs good defences and always watching for anything suspicious. Confidential computing emerges as a paramount paradigm in cloud security, establishing secure enclaves that process sensitive data within isolated, encrypted spaces. This innovative approach significantly mitigates the risk of unauthorized access, providing heightened data confidentiality beyond conventional security measures. Notably, even cloud service providers are barred from accessing data within these secure enclaves, fortifying defences against insider threats. The architecture enables the secure processing of encrypted data, maintaining encryption during usage and offering an additional layer of protection. This proves invaluable in scenarios requiring the analysis or processing of sensitive information, effectively reducing the attack surface for potential threats.